Pneumonia in patients with systemic lupus erythematosus: Epidemiology, microbiology and outcomes. (October 2018) - García-Guevara, G; Ríos-Corzo, R; Díaz-Mora, A; López-López, M; Hernández-Flores, J; Fragoso-Loyo, H; Ávila-Vázquez, J; Pulido-Ramírez, A L; Carrillo-Maravilla, E; Jakez-Ocampo, J; Sifuentes-Osornio, J; Llorente, L; et al.
Background and objective: Pneumonia remains the main cause of mortality in patients with systemic lupus erythematosus (SLE). The aim of the study was to establish the clinical characteristics, microbiology and risk factors for poor prognosis in patients with SLE and pneumonia. Methods: We reviewed medical records of patients with SLE (American College of Rheumatology criteria) and pneumonia who attended the emergency room in a single tertiary care center (January 2010–March 2015). We collected demographics, treatment and disease activity (SLEDAI-2K) data. Severity scales of pneumonia (CURB-65 (acronym for risk factors measured: confusion, urea nitrogen, respiratory rate, blood pressure, 65 years of age and older) and Pneumonia Severity Index (PSI)) were obtained. A negative composite outcome was defined as need for mechanical ventilation, septic shock or death secondary to pneumonia up to 30 days after discharge. We conducted a univariate and multivariable analysis. Results: We studied 158 patients (76% women) with 187 episodes of pneumonia. There were no differences in age, SLE duration, SLE activity, treatment or comorbidities between patients with negative composite outcome vs the other group. In 53 episodes, patients presented with a negative composite outcome. Of these, 46 (24.6%) required intubation, 13 (7%) developed shock and 12 (6.4%) died. The most common bacteria isolated was S. aureus, and we observed a high percentage of nonhabitual microorganisms. Fifteen percent of patients who presented with a negative outcome had low values on CURB-65 and PSI scales. Conclusion: Patients with SLE and pneumonia have a high risk of complications and present with a high percentage of nonhabitual microorganisms. Severity scales for pneumonia can misclassify as low risk SLE patients with poor prognosis.